Leila Khaled and her role in the Palestinian struggle (1944-1982) (Journal of the College of Basic Education, 2026)
Palestinian women have played a significant role in resisting the "Israeli" occupation and in defending the Palestinian cause from the beginning. This includes their participation in demonstrations against the Balfour Declaration in 1917, their rejection of the occupation, their participation in the 1936 revolution, their support for the fighters, and their provision of assistance. They endured the hardships of seeking asylum after 1948, and some were imprisoned. They also played a role in guerrilla activity inside and outside Palestine. In the 1960s, Palestinian women took up arms. Leila Khaled was one of the first women to carry a weapon. She is a model of the Palestinian woman who believed in armed struggle and was able to immortalize her image through her plane hijackings in 1969 and 1970, as well as her representation of Palestinian women in Arab and international forums by joining the General Union of Palestinian Women in 1974.